Do vocational colleges need social media? The Role of Firm and User Generated Content. - Iwan Mulyawan; Wahyu Rafdinal; Cahaya Juniarti; Sharnuke Asrilsyak (Journal of Business and Management Review, 2022)
The purpose of this paper is to investigate the role of social media in firm generated content (FGC) and user generated content (UGC) which bring impacts on perceived value and two types of intention, namely the intention to follow on social media and the intention to enrol in vocational colleges. Online survey was applied to collect the data from 452 respondents. The hypotheses were tested empirically using a variance-based structural equation model. The results point out that FGC and UGC are positively and significantly influential towards value. Perceived value discovered is influential significantly towards the consumers’ intention to follow social media, while UGC holds the highest importance compared to other constructs. Those results manifest the role of marketing in social media in which it will eventually influence the intention to follow on social media and to enrol in vocational colleges. These will give the inputs to the institutions to arrange social media contents which are able to increase the intention to follow in which it also boosts the intention to enrol. This research also adds the existing knowledge about the role of social media towards the intention to enrol.